Effecting Factors in Developing Accountancy in Libya - الدرويش بشير; الغالي عبدالمولى (Dirasat in Economics and Business, 2006)
The aim of this paper is to study the factors affecting the development of accounting profsssion within the Libyan environment. The accounting literature shows a number of factors that help largely in developing the accounting profession. These factors are: (professional institutions - accounting education - users of accounting information - institutional stability - sophisticated accounting systems - and culture). The paper concludes that none of these factors could help the development of the accounting profession in Libya; therefore, it requires many efforts to achieve the needed development.